Personal Computer Life Cycle Assessment Study: The Case of Western Australia - Sirait, Marudut; Biswas, Wahidul; Boswell, Brian (Berlin Institute of Technology, Berlin, Germany and Middle East Technical University, Ankara, Turkey, 2012)
The alarming growth of the information and communication technology (ICT) during the last decade has increased the awareness of environmental impacts associated with the use of personal computers (PC).Energy and materials use and e-waste disposal during the life cycle of ICT products need to be assessed in order to minimize the environmental impacts of ICT devices, particularly personal computer. This research utilizes a life cycle assessment (LCA) tool to identify the process (or processes) or “hotspot(s)” requiring mitigation strategies. The LCA of the PC’s takes into account all the stages from raw material extraction and production, manufacturing, transportation and use to disposal (cradle to grave). A desktop computer has been disassembled to develop a detailed life cycle inventory to carry out a LCA analysis. The LCA is constructed by SimaPro software version 7.3 and express with greenhouse gas and demand energy life cycle assessment method. The LCA shows that the use and manufacturing stages is the largest contributor to embodied energy and carbon footprint. In the manufacturing stage, LCA have been identified that the production of monitor is the greatest significantly in producing carbon footprint and embodied energy.